Public Debt Sustainability in Developing Asia: An Update - Benno Ferrarini; Arief Ramayandi (Asian Development Bank (ADB), 2015)
Our previous assessment of debt sustainability in developing Asia, conducted in 2011, found that the region's fiscal outlook was mostly benign. In this study we update the debt sustainability assessment, taking stock of the latest data and including a larger number of countries. With the benefit of hindsight, we assess the accuracy of our earlier debt ratio forecasts and the underlying macroeconomic assumptions. By and large, we find that standard debt sustainability analysis (DSA) represents a valid forecasting tool, able to predict debt ratios fairly accurately under reasonable assumptions and circumstances. Further, our fan chart analysis confirms the importance for stochastic analysis to integrate standard DSA, in order to capture heightened macroeconomic volatility, which we observe for some countries in the region. Looking forward to 2020, debt ratio projections confirm that the outlook remains benign for the region as a whole, country heterogeneity notwithstanding. On the issue of DSA methods and implementation, we emphasize the importance of macroeconomic forecast accuracy and suggest that volatility be captured by risk analysis tools that would optimally flank the standard DSA framework.
hdl:11540/5302
Keywords: E62; H63; H68; 330; debt-to-GDP ratio; fan charts; public debt sustainability; sovereign debt